A preliminary leaf epidermal and pollen morphology of some West African species of Desplatsia Bocq - Emmanuel O. Shokefun; Abiodun E. Ayodele; Emuobosa A. Orijemie (AOSIS, 2017)
Desplatsia is a genus made up of about four to eight species which are mostly trees native to tropical Africa. The leaf and pollen characters of three West African species of Desplatsia were investigated using light microscopy. The study was aimed at investigating the leaf epidermis and pollen morphology of the species to further enhance the understanding of the taxonomic relationships in the genus. The epidermal cells were isodiametric, polygonal to irregular with straight, curved to wavy anticlinal cell walls. The species were hypostomatic with anisocytic and staurocytic stomata types. The adaxial and abaxial walls of Desplatsia chrysochlamywere characterised by three-celled head multicellular glandular trichomes with highest number of cells and stomata and striated adaxial surface. The four-armed branched and stellate trichomes with the largest stomata size of 19.5 µm × 15.6 µm distinguished D. dewevrei from D. subericarpa in which the largest cells, lowest number of stomata and size were recorded. The pollen grains were medium in size 26.5 µm-47.5 µm, tricolporate with long colpi. However, the subprolate, baculate exine surface, small ora and lumen width separated D. chrysochlamy from D. dewevrei and D. subericarpa in which prolate, perforated exine surface and colpi margo were recorded. A key is provided for the identification of the species. Therefore, the ora size, lumen width, number of epidermal cell and stomata are additional taxonomic characters that can be used for species delimitation in the genus.